WEBSITE DESIGN APPLICATIONS IN COUNTER HP VAN Cellular USING PHP AND Adobe Dreamweaver CS3 - Irfan Fauzy; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Application websiteat Van Cellular counter is made to facilitate communityin getting an update on developments surrounding the mobile phone worldwhich is increasingly popular in the community by making applications mobile phone priceslist sold at one counter handphone, namely that Conter Cellular Mobile Vanprecisely located in Tangerang is Pamulang area. Application of this website is made byusing a merger between Adobe software Dreamweaver CS3 is used to design web pages,programming language Hypertext Preprocessor (PHP) which is a server side scriptinglanguage for web content together with the Hypertext Markup Language (HTML). Inparticular, PHP is designed to dynamic web form, it means php can form a view on requestrecent and very easy to use and learn.Keywords: Applications, Adobe Dreamweaver CS3, PHP